Pengaruh Kualitas Pelayanan, Suasana, dan Promosi Terhadap Kepuasan Pelanggan Smoking Barrels Craft Coffee - Aisiah Gesta Argarini; Jamaludin Khalid (Human Capital Development, 2022)
The purpose of this study is to determine whether the quality of service, atmosphere, and promotion affect the customer satisfaction of Smoking Barrels Craft Coffee. The population in the study were smoking barrels craft coffee customers. And the sample used in this study was 100 respondents using the purposive sampling method with a questionnaire that had been tested for validity and reliability. Analysis of multiple linear regression data with the help of IBM SPSS 20. The results of the t-test of this study show that the Quality of Service and Promotion has a significant effect on customer satisfaction with a significance value of 0.000. And the Atmosphere has no significant effect on customer satisfaction with a significance value of 0.530. Keywords : Quality of Service, Atmosphere, Promotion, Customer Satisfaction